Aspiration and poverty in an asymmetric information game: a case study of Southern Xinjiang. Issue 1 (20th November 2020) - Yao, Shujie; Wang, Jiefei
Abstract : Purpose: The purpose of this paper is to reveal the internal mechanism of the deviation of targeted poverty alleviation under the condition of asymmetric information. Design/methodology/approach: Introducing a traditional signaling game theory model with dynamic asymmetric information, this study uses a dataset covering 813 poor households from Southern Xinjiang, China, to theoretically and empirically study the effect of aspiration of the poor households on poverty alleviation. Findings: First, there exists asymmetric information between the poor households and village leaders. Second, the "short, arbitrary and fast" poverty alleviation approach may quickly pull people out of poverty, but it may also nurture a dependency culture where poor households lose their aspiration and ability to escape poverty through their own efforts. Third, due to long lasting universal state support, poor households in the national designated poor counties are less able and ambitious to escape poverty by themselves than their counterparts living in the national nondesignated areas. Originality/value: The research results show that pro-poor development policies should be upheld to improve the residual utility that can benefit all households as a result of the poverty alleviation campaign. Relevant policy recommendations are made for China's continuous effort to fight relative poverty beyond 2020.